Assessment of the efficiency and effectiveness of health care systems in European Union countries before and during the COVID-19 pandemic - Marek Biernacki (Frontiers in Public Health)
ObjectivesThe aim of this study was to determine the extent to which the national healthcare systems of European Union countries used their medical potential in the fight against COVID-19. The analyzed period covered the years before the pandemic 2009–2018 and the COVID-19 pandemic. The analysis was conducted for all European Union’s countries. It concerned the evaluation not only of the effectiveness of treatment, but also of the efficiency, i.e., the use of resources in healthcare systems.Study designDescriptive and analytical study on EUROSTAT data, Health Consumer Powerhouse, OECD Health Statistics, European Health Interview Survey (EHIS) and World Health Organization (WHO).MethodologyAn index was proposed to measure the quality of healthcare systems’ activities, which simultaneously assesses the effectiveness and efficiency of treatment. The treatment results depend not only on management, but also on financial resources. EHCI, HLY, % of unmet medical needs were used to assess the effectiveness of treatment. Efficiency was calculated using with the DEA method based on total healthcare expenditure per capita at purchasing power parity. The final assessment is based on the difference in the index value from the pandemic period and before the COVID-19 pandemic.ResultsThe healthcare systems of small EU countries coped most effectively and efficiently during the COVID-19 pandemic: Denmark (0.6), Estonia (0.5), Austria (0.5), Slovenia (0.3), and the Czech Republic (0.3). However, large and non-rich EU countries fared much worse: Spain (−0.8), Hungary (−0.7) and Poland (−0.4). This group also unexpectedly included the Netherlands (−0.3)—a small, wealthy country that coped poorly with the challenges posed by the COVID-19 pandemic.ConclusionBased on the analysis carried out in this paper, it can be concluded that the optimal (efficient and effective) use of medical resources did not depend only on the state of ownership and technological advancement of healthcare systems (!). The involvement of medical staff, society, and decisions of state authorities were equally significant.